Nuclear receptor Nur77 protects against oxidative stress by maintaining mitochondrial homeostasis via regulating mitochondrial fission and mitophagy in smooth muscle cell. (September 2022) - Geng, Na; Chen, Taiwei; Chen, Long; Zhang, Hengyuan; Sun, Lingyue; Lyu, Yuyan; Che, Xinyu; Xiao, Qingqing; Tao, Zhenyu; Shao, Qin
Abstract: Angiotensin II (AngII) induces disruption of mitochondrial homeostasis and oxidative stress. Nuclear receptor NR4A1 (Nur77) plays an important role in vascular smooth muscle cells (VSMCs) function. However, the role of Nur77 in AngII-induced mitochondrial dynamics and oxidative stress in VSMCs remains unknown. In an in vitro model of AngII-treated cells, we discovered that Nur77 knockout aggravated AngII-induced oxidative stress in VSMCs, whereas activation of Nur77 by celastrol diminished them. Concomitantly, disturbance of mitochondrial dynamics induced by AngII was further exacerbated in Nur77 deficient VSMCs compared to wild-type (WT) VSMCs. Interestingly, Nur77 deletion increased mitochondrial fission but not fusion as evidenced by upregulated fission related genes (Fis1 and Drp1) but not fusion (Opa1 and Mfn2) under AngII stimulation in VSMCs. Mechanically, Nur77 could directly bind to the promoter regions of Fis1 and Drp1 and repress their transcription. Furthermore, we observed that Nur77 additionally promoted mitochondrial homeostasis by increasing mitophagic flux in a transcription-independent manner upon AngII challenge. By using an in vivo model of AngII-induced abdominal aortic aneurysm (AAA), we finally validated the protective role of Nur77 involved in the mitochondrial fission process and mitophagic flux in aortas, which was correlated with the occurrence and development of AAA in AngII-infused mice. Our data defines an essential role of Nur77 in regulating oxidative stress by maintaining mitochondrial homeostasis in VSMCs via both transcription-dependent and transcription-independent manner, supporting the therapeutic potential of Nur77 targeting in vascular diseases. Graphical abstract: Unlabelled Image Highlights: Nur77 protected against AngII-induced oxidative stress and mitochondrial damage in VSMCs. Nur77 alleviated mitochondrial fission and restored mitophagic flux in VSMCs upon AngII stimulation. Nur77 maintained mitochondrial homeostasis via regulating mitochondrial fission and mitophagy.